Prospective study of hyperglycemia and its impact on the causation of severe exacerbations in chronic obstructive pulmonary disease (COPD) patients attending a tertiary care hospital - Kalyani, Kakumanu; Reddy, Chappidi Rajesh; Kumar, Muthineni Manoj (Journal of Applied Pharmaceutical Research, 2023)
Background: Hyperglycemic states are always associated with sudden onset of illnesses of both infectious and non-infectious nature. Chronic obstructive pulmonary disease is a chronic, lifelong suffering illness with sudden exacerbations. Objectives: To compare the affiliation of hyperglycemia with the chance of sudden exacerbations in sufferers with an established diagnosis of obstructive airway disease (COPD). Materials Methods: A total of 263 patients with an established diagnosis of COPD were taken into this observational study. The duration of the study extended between Jan. 2022 to July 2023. Sufferers were divided into 3 classes following the guidelines of the American Diabetes Association; those classes were: low HbA1c level class (n=102), moderate HbA1c level (n=83), and severe HbA1c level (n=74). Results: Among the 263 participants, 72 (27.4%) suffered severe exacerbation. The share of sufferers tormented by a minimum of one episode of intense and sudden exacerbation becomes extensively higher among participants with high (36.3%) and moderate HbA1c levels (24.7%) when compared with low HbA1c levels (22.6%). On the MCRA, high HbA1c levels (HR=2.65, 95% CI: 1.92–4.31; P<0.01) and moderate HbA1c levels (HR=2.06, 95% CI: 1.64–3.29; P<0.01). Participants with hyperglycemia were significantly associated with a higher risk of the next severe exacerbation compared with a euglycemic state. Conclusion: irrespective of current/previously established diagnosis of diabetes, hyperglycemic states are associated with a higher risk of severe exacerbation in patients with COPD.